A new species of Acyrthosiphon (Hemiptera, Aphididae) from France and Spain - Nafría, Juan M. Nieto; Aldea, Marta; Castro, Marta (Zootaxa, 2015)
A new species in one of the largest genera of Macrosiphini (Hemiptera, Aphididae), Acyrthosiphon pilosum sp. n., is described from apterous and alate viviparous females and oviparous females from French and Spanish Mediterranean localities, living on species of Ononis (Fabaceae), mainly O. natrix. The new species is characterized by the presence of many accessory setae on the ultimate rostral segment, and usually five setae on the first tarsal segments, a combination that is not present in any other known Acyrthosiphon species; in addition marginal tubercles are present on prothorax and several of abdominal segments 2–5.